The influence of phytohormones on the germination of apple pollen in the process of low-temperature storage - A. V. Pavlov; V. G. Verzhuk; M. N. Sitnikov; A. V. Shlyavas (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Under natural conditions, germinating pollen grains are in a complex multicomponent environment, including compounds of different chemical nature. The study of the action of phytoregulators on pollen germination is relevant, since in the long term it will help to improve the conditions of the germination medium, bring them closer to the natural ones and, as a result, increase the accuracy of the assessment of pollen viability.Materials and methods. The object of the study is pollen of the apple-tree образца Krasnolistnaya (Malus niedzwetzkyana Dieck, syn. M. sieversii (Ledeb.) M. Roem. var. niedzwetzkyana Likh.). The effect of phytohormones on apple-tree pollen germination in artificial nutrient medium was studied. Viability of pollen was assessed by germinating it in an artificial nutrient medium containing 10% sucrose and 0.8% agar-agar. Pollen was considered sprouted if its pollen tube in length exceeded the diameter of the pollen grain. Drops of pollen suspension in distilled water with added phytohormones in various combinations and concentrations were applied to the surface of the nutrient medium.Results. Two-factor dispersion analysis of the initial data made it possible to conclude that the greatest effect on pollen germination was provided by a combined action of the factors "stimulator concentration + illumination mode", under which there was an increased percentage of germinated pollen. The effect of only the stimulator's concentration and type on the number of germinated pollen grains was slightly less. And the least of all was the effect of the illumination mode on pollen grain viability, although the influence of this factor was also significant: p = 0.00562. Effective concentrations and combinations of phytohormones have been identified to increase germination of apple-tree pollen.